Wheel of fortune - Sony Computer Entertainment; THQ (Firm) (Agoura Hills, CA : THQ, 2012)
"Spin the wheel along with Pat Sajak and Vanna White on the virtual version of America's game!"--Amazon.com.
Title from label.
Number of players: 1-3, network players 2-3.
"Sony Computer Entertainment ; Sony Pictures."
"Blu-ray disc."
"PlayStation network"--Container.
Game developer credits from Gamespot.com.
Keywords: Video games; Television game shows; Questions and answers; Quiz shows